Eco-friendly mortars with addition of ornamental stone waste - A mathematical model approach for granulometric optimization. (1st March 2020) - Amaral, Lucas Fonseca; Girondi Delaqua, Geovana Carla; Nicolite, Micaela; Marvila, Markssuel Teixeira; de Azevedo, Afonso R.G.; Alexandre, Jonas; Fontes Vieira, Carlos Mauricio; Monteiro, Sergio Neves
Abstract: The increasing production of cementitious materials is generating considerable environmental impacts related to uncontrolled extraction of natural raw material for use as aggregates and the consumption of mostly fossil fuel based energy resources in the cement production. Moreover, Portland cement fabrication is highly energy intensive and releases one of the word's largest rate of CO2 emission, the main responsible for global warming and climate changes. Mortar is a typical example of a cementitious material associated with these environmental impacts. Among the possibilities for a mortar cleaner production stands the reduction of natural aggregates in their preparation, such as sand. Therefore, the objective of this work is to propose a methodology of partial replacement of the sand, commonly used for mortar production, by ornamental stone-processing waste. For this purpose, a mathematical model was applied to calculate the ideal particle size distribution for better packaging, which not only justify the replacement but also improve the technological properties of the mortar as a cementitious composite material. Mortars were made with a 1: 1: 6 compositions, associated with cement: lime: sand proportions. Amounts of 9 and 21 wt% of sand were replaced by waste, corresponding to values obtained through the mathematical model. These mortar precursor materials were characterized in terms of granulometry, chemical composition, pozolanicity as well as leaching and solubilization tests. The mortar technological characterization was performed both in its initial state (fresh density, air content and consistency) and past-cure hardened state (hardened density, flexural and compression stress). The results indicated the possibility of producing more sustainable and eco-friendly mortars. Moreover, this work also evidences that, in addition to the possibility of using ornamental stone waste as aggregate for cementitious materials, the particle size model is a non-empirical means to optimize aggregate mixtures and to improve the properties of waste incorporated eco-friendly mortars. Highlights: Ornamental stone waste can be classified as non-hazardous and non-inert. The Alfred model allowed the indication of the incorporation ratios of the waste to be 9 and 21 wt%. As in both formulations evaluated the produced mortars presented satisfactory performance. Mortars using the combination of sand with the waste is feasible from of the use of granulometric optimization.